2004
DOI: 10.1002/jnr.20081
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of TNFα‐inhibited neuronal cells by IGF‐1 involves Akt and c‐Jun N‐terminal kinases

Abstract: Proinflammatory cytokines, especially tumor necrosis factor alpha (TNFalpha), is a pleiotropic mediator of a diverse array of physiologic and neurologic functions and is upregulated during various inflammatory and neurodegenerative diseases. A common survival response during such situations is the increased expression of the hormone insulin-like growth factor 1 (IGF-1). Although it was thought previously that the mechanisms of TNFalpha and IGF-1 action were unrelated, it has been shown that low doses of TNFalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
(50 reference statements)
1
35
0
Order By: Relevance
“…PKB has previously been implicated in the signalling pathways of IL-1β and TNF-α [39,40]. Consistent with such a mechanism of action, the overexpression of kinase-dead PKB enhanced cytokine-induced apoptosis and necrosis, whereas constitutively-active PKB diminished these effects.…”
Section: Discussionmentioning
confidence: 56%
“…PKB has previously been implicated in the signalling pathways of IL-1β and TNF-α [39,40]. Consistent with such a mechanism of action, the overexpression of kinase-dead PKB enhanced cytokine-induced apoptosis and necrosis, whereas constitutively-active PKB diminished these effects.…”
Section: Discussionmentioning
confidence: 56%
“…We have previously shown that IGF-1 was involved in survival of neuronal cells via the JAK/STAT, PI3kinase, and JNK kinase pathways (12,13). However, as the target genes activated by IGF-1 in neuronal cells are not clear, we screened for various downstream molecules like BCL2, MYC, and cyclin D1 in neuronal cells following IGF-1 stimulation.…”
Section: Igf-1 Upregulates Cyclin D1 In Neuronal Cellsmentioning
confidence: 99%
“…IGF-1 has been shown to regulate cyclins, CDK protein expression, and retinoblastoma (Rb) protein phosphorylation in breast cancer cell lines (11). Our previous studies have shown that IGF-1 was a potent survival and rescue factor for dying neurons mediated by JAK/STAT, PI3kinase as well as JNK kinase pathway (12,13). However, the specific target genes involved in IGF-1 mediated cell survival in neuronal cells are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 activates various signaling pathways that enhance cell survival and proliferation, including pathways mediated by PI3-kinase/Akt (Xu et al, 1999;Kenchappa et al, 2004) and mitogenactivated protein kinases (MAPKs) (Chow et al, IGF-1 (100 ng/ml) was added 30 min later, and the cells were incubated for 6 h before lysis, SDS-PAGE, and immunoblotting to detect ZNF143 expression. In (A), the inhibitors were PD98059 (10 μM), SB203580 (10 μM), 10 μM SP600125 (10 μM), and wortmannin (100 nM).…”
Section: Phosphatidylinositol-3-kinase (Pi3-kinase) and Nadph Oxidasementioning
confidence: 99%